Perlindungan Hukum Benda Cagar Budaya dalam Upaya Pelestarian Kota Tua Jakarta - Adrey Fitri Zildjian Chandra Gupta; Endang Sutrisno (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is motivated by the urgency of legal protection for Jakarta's Kota Tua area, a historical heritage area threatened by physical damage and the pressures of urban development. The objective of the study is to analyze the effectiveness of the implementation of Law Number 11 of 2010 and regional regulations in ensuring legal certainty and preserving cultural heritage. The research method used is normative juridical with a descriptive analytical approach, utilizing primary and secondary legal materials through literature studies and field observations. The results indicate that legal protection by 2026 has evolved toward a collaborative model that integrates conservation with the Transit-Oriented Development (TOD) concept and digitalization through an e-Inventory system. However, the effectiveness of law enforcement is still hampered by issues of private ownership, high restoration costs without adequate incentives, and weak criminal sanctions. In conclusion, despite a comprehensive legal framework, the physical protection and substantive historical value of Jakarta's Kota Tua remain partial. The establishment of a single authority and the provision of concrete compensation to private building owners are necessary to ensure the sustainability of cultural heritage for future generations.